Sebaran Regional Industrialisasi Di Indonesia: Kinerja, Prospek Dan Kebijaksanaan Pengembangan - Soedjito, Bambang Bintoro (Center for Research and Community Services ITB, 1995)
Industrial sector, especially manufacture, has continuously shown a good performance with a double-digit rate of growth for the last 25 years. Unfortunately, not all of the regions are experiencing similar rate of growth able to take advantage of the rapid growth of industrialization. The development of manufacturing industry ¡s mostly concentrated ¡n certain locations in Jawa. Recently, however, the government has given more serious attention in making industrial development more equally distributed among the regions.